1, 3-Bis(cyanomethoxy)calix[4]arene capped CdSe quantum dots for the fluorogenic sensing of fluorene. Issue 23 (2nd March 2017) - Kumar, Rabindra; Arora, Meenu; Jain, Anil K.; Babu, J. Nagendra
Abstract : 1, 3-Bis(cyanomethoxy)- tert -butylcalix[4]arene (CAD) capped onto CdSe quantum dots (QDs) shows selective and sensitive fluorescence enhancement in the presence of fluorene among fifteen PAHs. Abstract : Capping of 1, 3-bis(cyanomethoxy)- tert -butylcalix[4]arene (CAD) onto CdSe quantum dots (QDs) was characterized by a fluorescence enhancement of the QDs ( λ em = 580 nm) upon surface interaction with the phenolic moiety of CAD. CAD@QD showed selective and sensitive 1.67 fold fluorescence enhancement in the presence of fluorene among fifteen PAHs. The fluorescence enhancement was characterized by monolayer adsorption of fluorene on to the surface of CAD@QD. The limit of detection for fluorene was observed to be 0.8 nM. This method was used and compared with detection of fluorene in spiked respirable dust (PM10 ) samples collected during an open biomass (stubble) burning event.